The influence of the gut microbiota on the development of food allergy in children (Research, Society and Development, 2021)
The gut microbiota, which is formed mainly early in life, plays a crucial role in the formation of the immune system and in food tolerance. Dysbiosis, which means an overgrowth of pathobiont bacteria, creates imbalance and inflammation of the gut microbiota, affecting its function. Because of this, there was interest in evaluating the influence of the microbiota on the development of food allergies in children, analyzing the interference of dysbiosis on the immune system, by the method of integrative review in the last 10 years, since there is an increase in the prevalence of food allergies in children in the last decade. This research is characterized as an integrative literature review, in which articles published in the last 10 years, selected through the inclusion criteria, were analyzed. It is based on the theme "The influence of the microbiota on the development of food allergy in children". Literature published in English, Portuguese and Spanish was sought as the study priority. The intestinal microbiota is directly related to the immune system, and malfunction of one is followed by imbalance of the other. Thus, the composition of a comprehensive and functional gut microbiota contributes to a more resilient immune system and can lead to a greater tolerance to food allergies. However, we conclude that dysbiosis is more conducive to the onset of allergies. Despite the genetic contribution, it has the contribution of environmental factors and hygienic factors that favor the onset of food allergy.